2024
DOI: 10.1111/imr.13325
|View full text |Cite
|
Sign up to set email alerts
|

Signals that control MAIT cell function in healthy and inflamed human tissues

Andrew J. Konecny,
Yin Huang,
Manu Setty
et al.

Abstract: SummaryMucosal‐associated invariant T (MAIT) cells have a semi‐invariant T‐cell receptor that allows recognition of antigen in the context of the MHC class I‐related (MR1) protein. Metabolic intermediates of the riboflavin synthesis pathway have been identified as MR1‐restricted antigens with agonist properties. As riboflavin synthesis occurs in many bacterial species, but not human cells, it has been proposed that the main purpose of MAIT cells is antibacterial surveillance and protection. The majority of hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 131 publications
0
1
0
Order By: Relevance
“…Recently, Konecny et al summarized MAIT cell signals that integrate different functions in healthy and inflamed tissues. They also highlighted the complexity of the computational exploration of cell–cell communication using single-cell data [ 28 ]. Fergusson et al reported that MAIT cells are characterized by high expression levels of multi-drug resistance protein 1 (MDR1), an ATP-binding cassette-multi-drug efflux protein.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Konecny et al summarized MAIT cell signals that integrate different functions in healthy and inflamed tissues. They also highlighted the complexity of the computational exploration of cell–cell communication using single-cell data [ 28 ]. Fergusson et al reported that MAIT cells are characterized by high expression levels of multi-drug resistance protein 1 (MDR1), an ATP-binding cassette-multi-drug efflux protein.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence shows that MAIT cells play a significant role in the immune response to SARS-CoV-2. In COVID-19 patients, circulating MAIT cells significantly decrease and become enriched in the airways ( 109 114 ). The remaining blood MAIT cells are activated, with increased CD69, CD38, HLA-DR, CD56, and granzyme B expression, along with decreased CXCR3 expression.…”
Section: Immunoregulatory Effectsmentioning
confidence: 99%
“…The remaining blood MAIT cells are activated, with increased CD69, CD38, HLA-DR, CD56, and granzyme B expression, along with decreased CXCR3 expression. Airway MAIT produce IL-17A and TNF, associated with chemokines like CXCL10 and CX3CL1 ( 109 , 112 ). Regarding clinical outcomes, current research shows inconsistent results.…”
Section: Immunoregulatory Effectsmentioning
confidence: 99%
See 2 more Smart Citations